Stabilizers of Natural Rubber Latex from Palm Oil - มูลชัย, ดริญญา; เอี่ยมรัมย์, อรุณศรี; ภัทชวงค์, ลักขณา; คงราม, อนุวัฒน์; แก้วศรีนวล, อัครสิริ (RMUTL Engineering Journal, 2019)
In this research, palm kernel oil soap and commercial palm oil soap were used as stabilizers for natural rubber latex. Palm oil soaps were prepared by sponification reaction. Ingredients of sponification reaction were palm oil, potassium hydroxide and water. Mechanical stability time (MST) of palm oil soap-stabilized natural rubber latex was compared with potassium oleate soap-stabilized natural rubber latex. The contents of stabilizers were varied at 0.10, 0.25 and 0.40 phr. It was found that 0.40 phr of stabilizers gave the highest MST. Potassium oleate soap showed the highest MST (> 3,600 seconds) followed by palm kernel oil soap (3,110 seconds) and commercial palm oil soap (2,190 seconds), respectively. Natural rubber product (Balloon) was also prepared by dip-molding process. The thickness of dip-molding product decreased with an increase of stabilizer concentration. The 0.40 phr of oleate soap-stabilized natural rubber latex gave the product having thickness comparable with the commercial product